Desain Solar Power Inverter pada Sistem Photovoltaic - Harmini, Harmini; Nurhayati, Titik (Universitas Semarang, 2020)
Solar power inverter is one of the main components in the PLTS system in order to produce the power or energy needed by the load. Solar power inverter is used to convert from DC energy (Direct Current) to AC (Alternating Current) to load. In this research a simulation of a solar power inverter system on a photovoltaic system will be designed. Simulation is done using SIMULINK-MATLAB software. Solar power inverter is designed using a boost converter as a controller and a Full-Bridge Inverter. Boost Converter is designed from 12VDC - 17 VDC to 300 VDC. Full Bridge Inverter produces AC voltage of 240 VAC with modulation index 0.8 and frequency 60 Hz. Total Harmonic Distortion is 46.07%. Power of Photovoltaic Solar panels generated at 3500 Watts at 1000 Watt / m2 irradiation conditions and temperature temperatures of 25 degrees Celsius.